Receptor for advanced glycation end products in relation to exposure to metal fumes and polycyclic aromatic hydrocarbon in shipyard welders - Lai, Ching-Huang; Chou, Chia-Chi; Chuang, Hsiao-Chi; Lin, Gu-Jiun; Pan, Chih-Hong; Chen, Wei-Liang (Ecotoxicology and environmental safety, 2020)
Advanced glycation end products (AGE) and the receptor for AGE (RAGE) have been found to be pivotal biomarkers to predict the risk of inflammation and oxidative stress. Limited evidence focuses on the influence of occupational exposure to polycyclic aromatic hydrocarbon (PAH) and metal fumes on AGE and RAGE in shipyard welders. Our aim was to determine the relationships among PAH, metal exposure, and inflammatory biomarkers. From September 1 to December 31, 2017, 53 welding workers (exposed group) and 29 office workers (control group) were enrolled in the study. Comprehensive workups included demographic characteristics, laboratory data, AGE, RAGE, Interleukin-6 (IL-6), tumor necrosis factor-α, PAH, and urinary metal concentrations. RAGE levels were measured by flow cytometric analysis. Urinary 1-hydroxypyrene (1-OHP) was used as a biomarker of exposure to PAH. Several metals were elevated in the personal fine particulate matter (PM2.5) samples, including Mn, Fe, V, Co, Zn, and Cu. The exposed group had significantly higher exposure to PM2.5 (p = 0.015), RAGE (p = 0.020), IL-6 (p = 0.008) than the control group. After adjusting for pertinent variables, there was still a significant and positive association between Ni level and AGE (β = 0.101; 95% CI, 0.031–0.172). Significant relationship between Cr and Cd levels and RAGE was observed (β = 0.173; 95% CI, 0.017–0.329; β = 0.084; 95% CI, 0.011–0.157, respectively). Participants with elevated 1-OHP level had higher odds of high RAGE level in the model 1 (OR = 3.466, 95% CI, 1.053–11.412) and model 2 (OR = 3.454, 95% CI, 1.034–11.536). The RAGE expression of participants was significantly associated with IL-6 levels in the fully adjusted model (β = 0.294; 95% CI, 0.083–0.732). Our findings highlighted that urinary metal levels and PAH were associated with increased AGE and RAGE formation in shipyard workers. Elevated serum RAGE might induce the production of proinflammatory cytokines and trigger ensuing inflammatory cascades. [Display omitted] •There is a significant association between Ni level and AGE.•Significant relationships of Cr and Cd levels with RAGE are observed.•Elevated RAGE expression is significantly correlated with increased IL-6 levels.